From Anthroponormativity to Creaturely Ethics: Rethinking Animals as Comparative Literary Subjects: Review of Dominic O’Key, Creaturely Forms in Contemporary Literature: Narrating the War against Animals - Ray, Sreyashi (Humanimalia, 2023)
Dominic O’Key, Creaturely Forms in Contemporary Literature: Narrating the War against Animals. New Horizons in Contemporary Writing. London: Bloomsbury, 2022. viii + 202 pp., 4 b/w illus. £85.00 (hb), £28.99 (pb).